Public administration in the conditions of the call of martial law - Izha, Mykola; Kurnosenko, Larysa (Public Administration and Regional Development, 2023)
The article analyzes the peculiarities of the functioning of the public administration system under martial law. It was found that the systemic factors that ensured the stability of the country in the conditions of active hostilities can be considered: developed entrepreneurship; advanced communications; decentralized economy management system; developed civil society; high level of openness of the state; high level of digitization of state services. It was determined that the basis of the stability of the state in the conditions of ongoing hostilities is the capacity of the public administration system, which is considered as the legal capacity of public authorities to carry out management activities aimed at organizing and streamlining life, ensuring the stability and development of society. The main components of the capacity of the public administration system have been determined: the system of providing high-quality and affordable administrative services, the system of professional public service, and the system of forming and implementing state policy based on analysis and communications with all interested parties. The main adaptation mechanisms of the specified components of the stability of the public administration system in the conditions of martial law were studied. It was determined that the main challenges that arose during the war and will affect the stability of the state in the post-war period are: security; resource; integration; information challenges. It was concluded that mitigating the impact of negative factors on the stability of the public administration system in wartime and post-war recovery will be facilitated by compliance with the gradualness of the initiated system reforms, public involvement in public decision-making processes, and development of the human capital of the public service.